The Inverse Relationship Between Psychological Well-Being and Death Anxiety Among Elderly Residents in Indonesian Nursing Homes - Purwaningsih, Rachmalia Yunnie; Kusumaningrum, Fitri Ayu (Unisia, 2025)
As global populations age, understanding psychological factors that influence how the elderly cope with mortality becomes increasingly critical. This study investigates the relationship between psychological well-being and death anxiety among older adults residing in nursing homes in Indonesia. The primary objective is to determine whether higher psychological well-being is associated with lower levels of death anxiety in late adulthood, particularly within institutionalized care settings. A total of 109 participants aged 60 and above were recruited from various eldercare institutions across Indonesia. Using a quantitative correlational design, data were collected through standardized instruments measuring psychological well-being and death anxiety. Statistical analysis employed Spearman’s rho to test the hypothesis due to non-normal data distribution. Findings revealed a significant negative correlation between psychological well-being and death anxiety. Participants with higher levels of well-being—characterized by self-acceptance, life purpose, and emotional resilience—consistently reported lower levels of fear related to death. These results align with existing theories suggesting that psychological resources buffer existential distress. Cultural and spiritual contexts, particularly in Indonesia’s collectivist and religious society, likely enhance this protective effect. The study also highlights the potential influence of gender, health status, and social connectedness as moderating variables. In conclusion, enhancing psychological well-being in institutional settings may serve as a strategic intervention to reduce death anxiety among the elderly. The findings contribute to gerontological psychology by offering culturally grounded insights and suggesting pathways for holistic, mental health-focused elder care.